Aid determinants in recent years - Park, Tae Jun (KDI School, 2011)
The purpose of this study is to identify and analyze the factors which may affect the allocation of bilateral aid from Korea in recent years. Both recipient countries’ factors and donor interests were considered as variable which may affect the allocation. Recipient countries’ factor variables explain their physical needs and political status, and donor interest variables explain the economic relationship between Korea and each recipient country. According to the regression result of the most reliable model which controlled the recipientcountry fixed effect and included all possible variables, Korean bilateral aid is responsive to population of recipient countries, export to recipient countries, import from recipient countries, and FDI investment in recipient countries.
Thesis(Master) --KDI School:Master of Public Policy,2011